Variability of cannabis potency in the Venice area (Italy): A survey over the period 2010–2012. Issue 1 (19th July 2013) - Zamengo, Luca; Frison, Giampietro; Bettin, Chiara; Sciarrone, Rocco
Abstract : Cannabis is the most widely used illicit substance globally, with an estimated annual prevalence in 2010 of 2.6–5.0% of the adult population. Concerns have been expressed about increases in the potency of cannabis products. A high tetrahydrocannabinol (THC) content can increase anxiety, depression, and psychotic symptoms, and can increase the risk of dependence and adverse effects on the respiratory and cardiovascular systems in regular users. The aim of this study was to report statistical data about the potency of cannabis products seized in the north‐east of Italy, in a geographical area centred in Venice and extending for more than 10 000 km 2 with a population of more than two million, by investigating the variability observed in THC levels of about 4000 samples of cannabis products analyzed over the period 2010–2012. Overall median THC content showed an increasing trend over the study period from about 6.0% to 8.1% (6.2–8.9% for cannabis resin, 5.1–7.6% for herbal cannabis). The variation in the THC content of individual samples was very large, ranging from 0.3% to 31% for cannabis resin and from 0.1 to 19% for herbal cannabis. Median CBN:THC ratios showed a slightly decreasing trend over the study period, from 0.09 (2010) to 0.03 (2012), suggesting an increasing freshness of submitted materials. Median CBD:THC ratios also showed a decreasing trend over the study from about 0.52 (2010) to 0.18 (2012), likely due to the increase in submissions of materials from indoor and domestic cultivation with improved breeding methods. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : THC levels of about 4000 samples of cannabis products analyzed over the period 2010‐2012 were investigated to report statistical data about cannabis potency in the north‐east of Italy, in a geographical area centred in Venice and extending for more than 10 000 km 2 with a population of more than two million.